The Feed Intake and Daily Weight Gain of Locally Sheep Fed with Amofer Palm Oil Plantation and Mill’s Byproduct-based Complete Feed - Hamdi Mayulu; Suhardi Suhardi (Chemical Engineering Diponegoro University, 2016)
Livestock development through innovation of complete feed (CF) technology which cheap and potential could be optimized through utilizing palm oil plantation and mill’s by-product. The objective of this research was to analyze the effect of complete feed formulated with palm oil plantation and mill’s by-product to the feed intake and daily weight gain of sheep. Male thin tailed sheep 9 months old with average live weight of 14.69 kg were used in this research. CF was formulated from ammoniated-fermented of palm frond, palm leave, empty fruit bunch, and palm pressed fiber which mixed with Centrosema sp., palm kernel cake, corn, rice bran, dried cassava waste pulp, molasses, mineral mix and salt. The study used completely randomized design which consisted of T1=10%, T2=12%, T3=14% and T4=16% of crude protein and total digestible nutrient (TDN) 64% with 4 repetitions. Data was analyzed using ANOVA at 95% significance level which followed by Duncan Multiple Range Test. The experiment showed that the level of protein content influenced the feed intake. The highest average of dry matter intake, organic matter intake, crude protein intake and TDN were 865.83 g/sheep/day, 750.60 g/sheep/day, 118.66 g/sheep/day and 555.96 g/sheep/day, respectively. The highest average daily weight gain was 174.18 g/sheep/day which produced at crude protein level of 14% (T3). The statistical analysis showed that T3 was significantly different to T1, T2 and T4. It can be concluded that complete feed formulated from palm oil plantation and mill’s by-product with appropriate level of crude protein content could increase the feed intake and daily weight gain of local sheep